2025-02-02

984: For Integers Modulo Prime Number Field, Prime-Number-th Power of Element Is Element

<The previous article in this series | The table of contents of this series | The next article in this series>

description/proof of that for integers modulo prime number field, prime-number-th power of element is element

Topics


About: field

The table of contents of this article


Starting Context



Target Context


  • The reader will have a description and a proof of the proposition that for the integers modulo prime number field for any prime number, the-prime-number-th power of each element is the element.

Orientation


There is a list of definitions discussed so far in this site.

There is a list of propositions discussed so far in this site.


Main Body


1: Structured Description


Here is the rules of Structured Description.

Entities:
\(\mathbb{Z} / p\): \(= \text{ the integers modulo prime number field }\)
\([z]\): \(\in \mathbb{Z} / p\)
//

Statements:
\([z]^p = [z]\)
//


2: Proof


Whole Strategy: Step 1: see that for each \([z], [z'] \in \mathbb{Z} / p\), \(([z] + [z'])^p = [z]^p + [z']^p\); Step 2: prove it inductively.

Step 1:

Let us see that for each \([z], [z'] \in \mathbb{Z} / p\), \(([z] + [z'])^p = [z]^p + [z']^p\).

The binomial theorem holds for any commutative ring, because it is only about distributability and commutativity.

So, \(([z] + [z'])^p = \sum_{j \in \{0, ..., p\}} {}_pC_j [z]^{p - j} [z']^j\), where \({}_pC_j = p! / (j! (p - j)!)\). But for each \(j \in \{1, ..., p - 1\}\), \({}_pC_j\) is a multiple of \(p\), because the denominator does not contain any \(p\) as a factor, which implies that \({}_pC_j [z]^{p - j} [z']^j = [0]\): for each \([z''] \in \mathbb{Z} / p\), \(p [z''] = p [1] [z''] = [p] [z''] = [0] [z''] = [0]\) and \(l p [z''] = l (p [z'']) = l [0] = [0]\).

So, \(([z] + [z'])^p = {}_pC_0 [z]^p [z']^0 + {}_pC_p [z]^0 [z']^p = [z]^p + [z']^p\).

Step 2:

Let us prove it inductively.

\([0]^p = [0]\).

Let us suppose that for each \(0 \le j \le k - 1\), \([j]^p = [j]\).

\([k]^p = [k - 1 + 1]^p = ([k - 1] + [1])^p = [k - 1]^p + [1]^p\), by Step 1, \(= [k - 1] + [1]\), by the induction hypothesis, \(= [k - 1 + 1] = [k]\).


References


<The previous article in this series | The table of contents of this series | The next article in this series>